Practical Guidelines for Optimization and Characterization of the Beckman Coulter CytoFLEX™ Platform. Issue 8 (9th March 2020) - Bhowmick, Debajit; Sheridan, Rachael T.C.; Bushnell, Timothy P.; Spalding, Kirsty L.
Abstract: Cytometer characterization is critical to define operational bounds within which the data generated are reliable and reproducible. Existing instrument optimization and characterization protocols were developed for cytometers relying on photomultiplier tubes (PMTs) for photon detection. Recently, instrument manufacturers have begun incorporating avalanche photodiodes (APDs) in place of PMTs. Differences in noise and signal amplification properties of the two detector types make many of the established PMT characterization protocols inappropriate for APD‐based instruments. In this article, we tested (three machines on two different sites) a variety of approaches to determine the best method for APD optimization on the Beckman Coulter CytoFLEX™ (CytoFLEX). From this, we propose easy‐to‐implement guidelines for CytoFLEX characterization and operation. These protocols are not designed to compare APD versus PMT based systems, nor are they designed to directly compare different CytoFlex instruments. Following these protocols will allow CytoFLEX users to characterize their instruments and help to identify optimized settings that allow for the generation of consistent and reproducible data. © 2020 International Society for Advancement of Cytometry